Subacute inflammatory processes and Chronic Bronchopulmonary: SIMPOSIUM - Martínez, José Luis; Puig, Roberto M; Delbene, Roberto; Bordes, Daniel; Rivas Chetto, C.; Zubiaurre, J; Stratta, A.; di Trápani, N; Sciuto, F; Louzán, R (Cirugía del Uruguay, 2004)
Introducción Jose Luis Martinez In 32 years of experience in Thoracic Surgery (1970 - 2002) we have operated 56 patients for subacute and chronic bronchopulmonary inflammatory processes. In that period we have treated 21 primitive pulmonary suppurations and 35 bronchiectasis. Despite their different origins all these entities have pathological alterations common where fibrosis predominates, dilations bronchial, presence of cavities and circulation anomalous systemic that are at the base of suppurative clinical manifestations, hemorrhagic or secondary aspergillary fungal infection.